«Війна» після війни: боротьба проти бандитизму на Сумщині у другій половині 1940-х – на початку 1950-х років - Рожкова, Л.І. (Сіверщина в історії України, 2020)
Стаття присвячена боротьбі працівників органів внутрішніх справ проти бандитизму на території Сумської області у повоєнні роки. Проаналізовано соціально-економічну ситуацію в Україні. З’ясовано, що причини зростання злочинності мали як об’єктивний, так і суб’єктивний характер. Соціальну напруженість посилив голод 1946–1947 рр. Особливістю криміногенної ситуації на Сумщині була діяльність організованих банд, зокрема, у північних лісових районах області. Визначено мету та основні заходи з реорганізації органів внутрішніх справ у другій половині 1940-х – на початку 1950-х рр. Досліджено напрями та результати діяльності правоохоронців з ліквідації злочинних угрупувань на території області. Встановлено, що на початок 1950-х рр. на Сумщині було ліквідовано майже усі бандитські угрупування; разом з тим, загальний рівень злочинності залишався високим. The article is dedicated to the fight against bandit carried by law enforcement officers in the Sumy region during the post-war years. Thus, the social-economic situation in Ukraine had been analyzed. It was found that the reasons for the increase in crime were both objective (economic ruin, poor living conditions) and subjective (dehumanization of public relations, a large number of illegal weapons). The social tension was exacerbated by the Famine of 1946 - 1947. The increase in crime, and in the number of serious crimes (murders, robberies) were observed in all regions of Ukraine. In 1947, the death penalty was renewed. Moreover, the need for the reorganization of law enforcement agencies, in particular, the creation of the units in the Ministry of Internal Affairs of the Ministry of Internal Security under the Ministry of State Security of the USSR, not only to improve the work of the police, but also to assist the State Security Agencies in the execution of punitive functions. The peculiarity of the criminogenic situation in Sumy region was the activity of organized gangs, in particular, in the Northern Forest districts of the region. The directions and results of the activity of law enforcement agencies on the elimination of criminal groups in the region had been investigated. Futhermore, the features of the process of combating banditry with the involvement of agents, service dogs, technical devices had been highlighted. It had been found that in some cases the criminal motives of banditry were combined with political ones, in particular when it came to attack on Soviet functionaries, who were revenged for their abuses during the disintegration (so called «rozkurkulennia») and the Holodomor in the early 1930s. In addition, it had been established that in the early 1950’s almost all the gangs were eliminated in the region, while the overall crime rate remained high.